Setting Up an Ethical Oncofertility Practice in Developing Countries - Linkeviciute, Alma; Boniolo, Giovanni; Peccatori, Fedro A. (Bangladesh Journal of Bioethics, 2015)
Fertility preservation for cancer patients is a relatively new field in medicine which requires interdisciplinary approach. Improving therapies and rising survival rates require to consider patients quality of life after cancer is cured which is relevant personal issue regardless of the individual income and the level of development of the country of origin. Fertility preservation offers possible solution but also raises ethical questions. We provide a summary of ethical principles embodied in professional guidelines together with options and restrictions to access fertility preservation in developing countries. We also make a suggestion that oncofertility counselling could be a pillar to address fertility preservation issues in cancer patients. Our proposed decisional support model is patient centred and focuses on patient values, personal philosophy and view of life emphasizing sensitivity to individual patients needs and wishes. Some fertility preservation concerns in oncology might be addressed mirroring already available expertise while some others will call for innovative and region specific solutions. Therefore, in addition to our proposal we also provide a list of organisations working in oncofertility field. DOI: http://dx.doi.org/10.3329/bioethics.v5i3.21532 Bangladesh Journal of Bioethics 2014 Vol.5 (3): 6-17.